(untitled) (Research, Society and Development, 2020)
Chitosan is a biopolymer with wide application in the cosmetic, textile, food and agriculture areas. In this work chitosan nanoparticles (CNP) was produced by ionic gelation and used as coating in starch (TPS) and poly(lactic acid) (PLA) sheets produced by thermoplastic extrusion. In the CNP the average diameter, the morphology by transmission electronic microscopy and the antimicrobial activity against the microorganism Salmonella typhimurium, Staphylococcus aureus, Penicillium expansum and Aspergillus ochraceus were determined. In the TPS/PLA sheets coated with CNP the mechanical properties and water vapor permeability (WVP) were determined. The CNP were successfully produced by ionic gelation method, the average diameter was 146.9 nm, the polydispersity index was 0.281 and showed spherical shape. The CNP did not show antimicrobial activity against the microorganism studied. Furthermore, their use as a coating on TPS/PLA sheets did not alter the mechanical and water vapor barrier properties and thickness.